Pemanfaatan Media Sosial Tik Tok sebagai Media Promosi Brand El Pietro - Putri Syifa; Rini Rinawati (Bandung Conference Series: Communication Management, 2022)
Abstract. El Pietro Coffee was founded in 2019. El Pietro introduces and utilizes Tik Tok social media to develop brand awareness. The Tik Tok @pietro.coffee account itself already has 13 thousand followers. The purpose of this study was to determine the implementation of the use of Tik Tok social media as a promotional media, to find out the forms of barriers to the use of Tik Tok social media as a promotional media, and to find out the reasons for choosing Tik Tok social media as a promotional media. This study uses a qualitative research method, using a case study approach. This study uses informants consisting of marketing El Pietro Coffee, Operational El Pietro Coffee. Data collection techniques used are observation, interviews, and literature study. The results obtained show the implementation of the use of Tik Tok social media on the @pietro.coffee account as a brand promotion media, using advertising, public relations and publicity, event and experience, and online and social media marketing in its promotional activities. Utilization of Tik Tok social media as a promotional medium to create and increase brand awareness. El Pietro Coffee stated that there are obstacles in the form of peopleware and hardware, namely the uncertainty of the Tik Tok algorithm in determining prime-time in each Tik Tok user account. The reason El Pietro Coffee uses Tik Tok social media as an online business tool is because currently the world is still being hit by the Covid-19 pandemic where the mobility of community activities outside the home still has to be limited, so El Pietro Coffee decided to use Tik Tok as a platform to promote brands, create and increase brand awareness, expand product target market, and get new target market. Abstrak. El Pietro Coffee berdiri pada tahun 2019. El Pietro memperkenalkan dan memanfaatkan media sosial Tik Tok untuk mengembangkan brand awareness. Akun Tik Tok @pietro.coffee sendiri sudah memiliki 13 ribu pengikut. Tujuan dari penelitian ini adalah untuk mengetahui pelaksanaan pemanfaatan media sosial Tik Tok sebagai media promosi, untuk mengetahui bentuk hambatan pada pemanfaatan media sosial Tik Tok sebagai media promosi, dan untuk mengetahui alasan mengapa memilih media sosial Tik Tok sebagai media promosi. Penelitian ini menggunakan penelitian metode kualitatif, dengan menggunakan pendekatan studi kasus. Penelitian ini menggunakan informan yang terdiri dari marketing El Pietro Coffee, Operational El Pietro Coffee. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan studi pustaka. Hasil yang diperoleh menunjukkan pelaksanaan pemanfaatan media sosial Tik Tok pada akun @pietro.coffee sebagai media promosi brand, menggunakan advertising, public relations and publicity, event and experience, dan online and social media marketing dalam kegiatan promosinya. Pemanfaatan media sosial Tik Tok sebagai media promosi untuk menciptakan dan meningkatkan brand awareness. El Pietro Coffee mengemukakan adanya hambatan dalam bentuk peopleware dan hardware yaitu tidak menentunya alogaritma Tik Tok dalam penentuan prime-time di setiap akun pengguna Tik Tok. Alasan El Pietro Coffee memanfaatkan media sosial Tik Tok sebagai sarana bisnis online dikarenakan saat ini dunia masih sedang dilanda pandemic Covid-19, maka El Pietro Coffee memutuskan untuk memanfaatkan Tik Tok sebagai platform untuk mempromosikan brand, menciptakan dan meningkatkan brand awareness, memperluas target pasar produk, dan mendapatkan target pasar yang baru.